2000
DOI: 10.1093/aje/152.10.940
|View full text |Cite
|
Sign up to set email alerts
|

Use of Coping Strategies and Breast Cancer Survival: Results from the Black/White Cancer Survival Study

Abstract: This analysis was designed to evaluate the association between coping strategies and breast cancer survival among Black and White women in a large population-based study. A total of 442 Black and 405 White US women diagnosed with invasive breast cancer during 1985-1986 and actively followed for survival through 1994 were administered a modified Folkman and Lazarus Ways of Coping questionnaire. Coping strategies were characterized via factor analyses of the responses. Hazard ratios associated with coping strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
131
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 171 publications
(142 citation statements)
references
References 40 publications
9
131
0
2
Order By: Relevance
“…In this study, the unfavourable effect of emotional defensiveness was strong and persistent. This agrees with previous findings on the favourable effect of more expression and less suppression of emotions on breast cancer progression (Reynolds et al, 2000) and the unfavourable effect of antiemotionality in cancers (Grossarth-Maticek et al, 1985;van der Ploeg et al, 1989). Our scale evaluated control of anger in particular (Swan et al, 1992), and we found it to be associated with the Anger Control trait of the highly validated AX/Scale, which was, however, not predictive on breast cancer survival (In corresponding data concerning localised melanoma (Lehto et al, 2006), we found Anger-in and Anger Control traits to predicted worse survival.).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In this study, the unfavourable effect of emotional defensiveness was strong and persistent. This agrees with previous findings on the favourable effect of more expression and less suppression of emotions on breast cancer progression (Reynolds et al, 2000) and the unfavourable effect of antiemotionality in cancers (Grossarth-Maticek et al, 1985;van der Ploeg et al, 1989). Our scale evaluated control of anger in particular (Swan et al, 1992), and we found it to be associated with the Anger Control trait of the highly validated AX/Scale, which was, however, not predictive on breast cancer survival (In corresponding data concerning localised melanoma (Lehto et al, 2006), we found Anger-in and Anger Control traits to predicted worse survival.).…”
Section: Discussionsupporting
confidence: 93%
“…The impact of psychosocial factors on cancer progression has been investigated in a number of studies (Greer et al, 1979(Greer et al, , 1990Pettingale et al, 1985;Gross, 1989;Spiegel et al, 1989;Forsen, 1991;Barraclough et al, 1992;Blanchard et al, 1995;Maunsell et al, 1995;Dolbeaut et al, 1999;Watson et al, 1999;Butow et al, 2000;Reynolds et al, 2000;Spiegel, 2001;Petticrew et al, 2002;Garssen, 2004) and many of these have dealt with breast cancer (Greer et al, 1979(Greer et al, , 1990Pettingale et al, 1985;Spiegel et al, 1989;Forsen, 1991;Barraclough et al, 1992;Maunsell et al, 1995;Watson et al, 1999;Butow et al, 2000;Reynolds et al, 2000;Garssen, 2004). However, the contributing factors are uncertain, and there is also a lack of understanding of the psychological processes and the psychobiological mechanisms involved (Garssen and Goodkin, 1999).…”
mentioning
confidence: 99%
See 3 more Smart Citations